The creativity factors of innovation team - Zabielavičienė, Irena (Business: Theory and Practice, 2019)
The article presents the concept of creativity factors and the point of view  on the directions of the analysis of creativity factors by different authors. It investigates the impact on the creativity of firm organizational factors and personal characteristics of the employees working in innovation teams. The article asserts that the more efficient utilization of the creative potential in the innovation teams of the Lithuanian manufacturing companies should be related to the implementation of spiritual organi-zational behavior principles in practice. It reveals what differentiates spiritual organizations from non-spiritual ones. The factors of spirituality of the organizational behavior are analyzed. The author of the article identifies three main characteristics of the innovation team members: openness, perception, high normal quality degree. The present study defines openness, perception, high moral quality degree, and presents the results of the analysis of the above factors on the creativity of an employee working in the innovation team. The impact of the employees’ moral development  consists of four stages. The article determines the effect of the employees’ moral development level on the creativity factors using econometric methods. This analysis reveals that the high moral quality degree of an employee, which is related to his/her aspiration of perfection, has the largest impact on his creativity. The effect of openness, which relates to the ability of an individual to question the accepted views,  has a substantial effect as well. Perception, which is related to the individual’s aspiration of knowledge, is the least important factor of creativity. Econometric methods are used to determine the effect of the employee’s moral development level on creativity factors. The analysis based on econometrics shows that the level of the moral development of an employee working in an innovation team has an impact on his/her openness, which reflects his/her ability to question their own views, and on his/her high moral quality degree reflecting his/her aspiration  for perfection. The employee’s perception reflecting his/her aspiration  for knowledge is not correlated with his/her moral development level. The article suggests a model of the analysis of the creativity of employees’ working in the in-novation team. This model incorporates the following factors: high moral quality degree and openness, which depend on their moral development and perception. Knowing the characteristics of the employees’ moral development level and their impact on the aspiration  for perfection and ability to question accepted beliefs helps to form better innovation teams. It is normal for a team to have a blend of different levels. It is most important what the level of the majority is and what status and role in the team the members with a higher moral development level have. This does not only determine the criteria that team members will use to make decisions in their areas of professional competence, but also set the manner of co-operation and formulate the norms.Article in Lithuanian.Inovacijų komandos kūrybingumo veiksniaiSantrauka. Straipsnyje pateikiama kūrybingumo veiksnių samprata ir įvairių autorių požiūris į kūrybingumo veiksnių tyrimo kryptis. Nagrinėjama įmonių organizacinių veiksnių ir darbuotojų, dirbančių inovacijų komandose, asmeninių savybių įtaka jų kūrybingumui. Teigiama, kad geresnis kūrybinio potencialo naudojimas šalies pramonės įmonių inovacijų komandose turėtų būti siejamas su dvasingos organizacinės elgsenos principų įgyvendinimu praktikoje. Atskleidžiama, kuo skiriasi dvasingos organizacijos nuo nedvasingų, nagrinėjami organizacinės elgsenos dvasingumo veiksniai. Straipsnio autorė išskiria tris pagrindinius inovacijų komandos nario, kaip asmenybės, kūrybingumo veiksnius: atvirumą, suvokimą ir idėjiškumą. Pateiktos atvirumo, suvokimo ir idėjiškumo sampratos, šių veiksnių įtakos darbuotojo, dirbančio inovacijų komandoje, kūrybingumui analizės rezultatai. Darbuotojų asmeninių savybių įtaka kūrybingumui nagrinėjama kartu įvertinant jų moralinės raidos lygį. Pateiktas darbuotojų moralinės raidos lygio klasifikavimo, išskiriant keturias jo stadijas, loginis pagrindimas. Taikant ekonometrinius metodus nustatyta darbuotojo moralinės raidos lygio įtaka kūrybingumo veiksniams. Tyrimo rezultatai parodė, kad didžiausią įtaką kūrybingumui turi darbuotojo idėjiškumas, atspindintis tobulumo siekį. Reikšmingą įtaką turi ir atvirumas, atspindintis asmenybės gebėjimą kvestionuoti susiformavusias pažiūras. Suvokimas, atspindintis asmenybės pažinimo siekį, yra mažiausiai reikšmingas kūrybingumo veiksnys. Darbuotojo moralinės raidos lygio įtaka kūrybingumo veiksniams nustatyta taikant ekonometrinius metodus. Atliktas tyrimas parodė, kad darbuotojo, dirbančio inovacijų komandoje, moralinės raidos lygis turi įtakos jo atvirumui, atspindinčiam gebėjimą kvestionuoti savo pažiūras, ir idėjiškumui, atspindinčiam tobulumo siekį. Darbuotojo suvokimas, atspindintis pažinimo siekį, nekoreliavo su jo moralinės raidos stadija. Darbuotojo, dirbančio inovacijų komandoje, kaip asmenybė, kūrybingumui tirti siūlomas modelis, jungiantis šiuos veiksnius: idėjiškumą ir atvirumą, kurie priklauso nuo jo moralinės raidos lygio, bei suvokimą. Žinant darbuotojų moralinės raidos lygio charakteristikas ir jų įtaką tobulumo siekiui bei gebėjimui kvestionuoti susiformavusias pažiūras, galima tikslingiau formuoti inovacijų komandas. Natūralu, kad komandoje susidaro įvairių lygių mišinys. Svarbu, kokio lygio yra dauguma ir kokį statusą ir vaidmenį komandoje užims aukštesnės moralinės raidos lygio nariai. Nuo to priklauso ne tik kokiais kriterijais remsis komandos nariai, priimdami sprendimus profesinės kompetencijos srityje, bet ir kaip bendraus, kokios susiformuos normos.Reikšminiai žodžiai: inovacijų komanda, kūrybingumas, suvokimas, atvirumas, idėjiškumas, moralinė raida, dvasingos organizacijos principai.